1986
DOI: 10.1002/mrc.1260240803
|View full text |Cite
|
Sign up to set email alerts
|

15N NMR: Iminothiol‐thioamide tautomerism of 2‐mercaptobenzazoles and 1‐methyl‐2‐mercaptoimidazole

Abstract: lSN NMR spectra of a number of 2-mercaptoazoles were obtained and the position of the iminothiol-thioamide prototropic tautomeric equilibrium was determined. Because of the large chemical shift difference of cu 100 ppm between the iminothiol and thioamide nitrogen atoms, the I5N chemical shifts of the S-methyl and N-methyl analogs of each tautomer provided reasonable chemical shift models for the same nitrogen atom in the tantomers. Only a small correction for an N-methyl effect was required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 19 publications
(4 reference statements)
4
26
0
Order By: Relevance
“…1, 2004 tautomer with the protonated N-atom. 7,8 Most of the electron density of the oxygen is in resonance with the aromatic ring making it a poor donor atom. Although S↔N linkage isomerism in bzoxs complexes is possible, no evidence has ever been published.…”
Section: N(o)sr]mentioning
confidence: 99%
“…1, 2004 tautomer with the protonated N-atom. 7,8 Most of the electron density of the oxygen is in resonance with the aromatic ring making it a poor donor atom. Although S↔N linkage isomerism in bzoxs complexes is possible, no evidence has ever been published.…”
Section: N(o)sr]mentioning
confidence: 99%
“…The 1 H, 13 C, and 15 N NMR spectra, plus a 1 H-15 N (HMBC) spectrum, were recorded in DMSO-d 6 on a Bruker Avance 600 spectrometer operating at 600. [3,4] confirmed that the used MMI ligand was present in DMSO solely as thione tautomer.…”
Section: Nmr Studiesmentioning
confidence: 69%
“…It also showed sharp strong absorbtion at 1664-1692 cm -1 corresponding to vinylic double bond, and a broad band at 3459-3466 cm -1 corresponding to the -OH iminol, the tautomeric forms of amide. 19 Mass spectra showed correct molecular ion peaks and fragmentation pattern. Isotopic patterns were utilized to confirm the presence of chloro substituent.…”
Section: Discussionmentioning
confidence: 99%